Ecopesantren As Empowering Boarding Boarding Communities Through Land Conversion Movement - Anjani, Sari Tri; Syamsiah Badruddin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The problem of limited access to fulfill food needs, especially for pesantren communities during the COVID-19 pandemic, led Pondok Pesantren Hajar Aswad, Sunan Pandanaran Foundation to initiate a land conversion movement to promote food security. With the concept of greenhouses, empty land is converted into food source land by implementing the aquaponic cultivation method. This research aims to understand how the ecopesantren program can empower the pesantren community (santri, pesantren residents, surrounding communities) through land conversion movements, as well as a new form of social movement. This research uses a qualitative method with a case study research type. The results of this study show that (1) the application of the greenhouse method as a form of conversion of vacant land by pesantren has succeeded in realizing food security and economic independence. (2) the pesantren community participates in each other and has the same role in its management. (3) This management has a socio-ecological impact, namely increasing social awareness and improving the economy of the pesantren community, as well as contributing to the welfare and preservation of the surrounding environment. This shows that the pesantren community is empowered through the ecopesantren program, one of which utilizes the land by carrying out the movement to convert vacant land into greenhouses using the aquaponics system to support food security and encourage economic independence in the pesantren community.